The pathophysiology of rapid fluctuations in mental status associated with olanzapine: A case report - Torrico, Tyler J. (Frontiers in Psychiatry, 2022)
Background Olanzapine toxicity is reported to be a rare but specific phenomenon characterized by rapid fluctuations between somnolence and agitation, which has been referred to as “agitation despite sedation.” A similar phenomenon is observed as an adverse reaction of the long-acting injectable olanzapine formulation, which has been referred to as “delirium/sedation syndrome.” Case presentation This case report describes a 48-year-old man diagnosed with schizophrenia who experienced rapid fluctuations between somnolence and agitation during a cross-titration of olanzapine to clozapine. The patient had normal serum levels of both medications and the symptoms resolved with the discontinuation of olanzapine. Conclusion Rapid fluctuations in mental status between somnolence and agitation are not clearly described among other antipsychotics, and it is possible that this phenomenon may be specific to olanzapine. The findings of this case report suggested that this phenomenon was likely the result of the oversaturation of (H1) and (M1) receptors.